If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 + 3y = 18 Remove the zero: 3y = 18 Solving 3y = 18 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '3'. y = 6 Simplifying y = 6
| 5y-12=73 | | 1=.5x | | -4(3-6d)=(2d-2) | | 64=4w | | y=.5(-10) | | x*z= | | (8k/(k-3))+1=((6k-2)/(k^2-4k+3)) | | 12x+2y=-6 | | -6n+19=-5n-1 | | -9=-y+6 | | x-3/7x-21 | | (7/x)=(21/24) | | 2x=360/4 | | 9=-y+6 | | (5/4)=(x/16) | | x=-0+6 | | 0=-y+6 | | y=21-5 | | 0.3x+5=6.5 | | 5=-6x | | 3*x-8=96 | | .02(3-(-6))-.04(-6+2)= | | 1/5/7/10 | | -6x(3x-4)=4x-2(x+2) | | 5x+2y=49.30 | | -3-2y=-5 | | 3(7-n)=-3(n-9) | | x-2(-4)=-5 | | 2(0)+y=2 | | 12-8x=86-22x | | -4x-9y-5=0 | | -6=.5x-3 |